Strategic adaptation to climate change in Europe - Sam Fankhauser; Raluca Soare (European Investment Bank (EIB), 2012)
This paper analyses the priorities and challenges for Europe as it adapts to the impacts of climate change. Whatever the ultimate level of warming we will experience, adaptation will be a permanent feature of decision making from now on. As such it is important to go about it in a strategic, rational way. A strategic approach to adaptation involves setting priorities, both spatially (where to adapt) and inter-temporally (when to adapt). The paper reviews the available evidence on Europe's exposure, sensitivity and adaptive capacity to indicate geographic adaptation priorities. In terms of intertemporal priorities, it recommends fast-tracking two types of action: Win-win measures that yield an immediate return, such as water efficiency, and strategic decisions on infrastructure and planning that have long-term consequences for Europe's vulnerability profile. A strategic approach to adaptation involves careful project design to ensure adaptation measures are cost-effective (how to adapt). An important complication in this respect is the deep level of uncertainty that still exists about future climate change at the local level. This puts a premium on flexible designs that can be adjusted when new information becomes available. The final element of a strategic approach to adaptation is division of labour between the state on the one hand, and private actors (households and firms) on the other (who should adapt). The paper argues that the traditional functions of the state - the provision of public goods, creation of an enabling environment and protection of the vulnerable - also apply to adaptation. – – In diesem Arbeitspapier werden die Prioritäten sowie die Schwierigkeiten analysiert, die sich für Europa bei der Anpassung an die Auswirkungen des Klimawandels ergeben. Unabhängig davon, wie stark die Erderwärmung letztendlich ausfällt, wird die Anpassung von nun an bei allen Entscheidungsprozessen eine Rolle spielen müssen. Es ist daher notwendig, in dieser Hinsicht strategisch und rational zu agieren.
Keywords: H12; H43; H84; Q54; 330